Heat treatment process method for regulating and controlling strength and plasticity of TA18 titanium alloy
By rolling and insulating and quenching treatment in TA18 titanium alloy, the isometric α phase and needle-shaped α′ martensite phase are formed, which solves the problem of the plasticity of TA18 titanium alloy in the prior art, and improves its strength and plasticity matching reduces crack sensitivity.
Patent Information
- Application Number
- CN202411498882.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art after adjusting the annealing temperature of TA18 titanium alloy, it causes its plasticity or toughness to decrease, increasing the crack sensitivity of titanium alloy and limiting its production and application.
By rolling the forged TA18 titanium alloy at room temperature, and insulated at 25~30°C below its β phase change point for 2~2.5 hours, quenching to room temperature to form an equiaxed α phase and a needle-shaped α'Marves The body phase is controlled to control the temperature and time of the insulation treatment to improve the alpha phase recrystallization and beta phase transition of the titanium alloy.
The high strength and high plasticity characteristics of TA18 titanium alloy are achieved, and the strength and plasticity matching are reduced, and the crack sensitivity of titanium alloy is reduced. The yield strength is 600~700MPa, the tensile strength is 700~800MPa, and the elongation after break is 20~30%. .
Smart Images

Figure CN119307846A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of heat treatment of titanium alloys, and more specifically, to a heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy. Background Art
[0002] TA18 titanium alloy (Ti-3Al-2.5V alloy) is a near-α-type titanium alloy with low aluminum equivalent. It has the characteristics of low density, high specific strength, excellent cold bending forming ability, excellent welding performance and good corrosion resistance. It is an ideal material for making titanium tubes. The alloy has been widely used in aircraft hydraulic and fuel pipeline systems and ship seawater pipeline systems. Improving the mechanical properties and load-bearing capacity of the alloy is a key research topic in the field of titanium tube research and development.
[0003] The mechanical properties of titanium alloys are extremely sensitive to their microstructures, so regulating the microstructure is an effective way to optimize the room temperature strength and plasticity of near-α titanium alloys and improve the comprehensive mechanical properties of the material. In terms of regulating the mechanical properties of TA18 titanium alloys, the existing technology mainly uses annealing treatment after cold deformation to adjust the annealing temperature of TA18 titanium alloys to obtain the best strength-plasticity match. However, while this adjustment method improves the strength of the alloy, it is usually accompanied by a decrease in plasticity or toughness, increases the crack sensitivity of the titanium alloy, is not conducive to the subsequent cold forming of the TA18 titanium alloy, and limits the production and application of TA18 titanium alloys. Summary of the invention
[0004] The purpose of the present invention is to provide a heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy, which is used to solve the technical problem that after adjusting the annealing temperature of TA18 titanium alloy, the plasticity or toughness of the titanium alloy decreases, and the crack sensitivity of the titanium alloy increases. In view of this, the present invention is implemented through the following scheme.
[0005] In a first aspect, the present invention provides a heat treatment process for regulating the strength and plasticity of TA18 titanium alloy, comprising: Obtaining a forged TA18 titanium alloy, wherein the microstructure of the TA18 titanium alloy includes an α phase and a β phase, with the α phase as a matrix; The TA18 titanium alloy is subjected to a rolling process at room temperature; The TA18 titanium alloy is heat treated at 25-30° C. below its β transformation point for 2-2.5 hours and then quenched to room temperature. The microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase.
[0006] Compared with the prior art, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, a plate-shaped titanium alloy with high strength characteristics can be obtained by rolling the forged TA18 titanium alloy. During the rolling process, the strength of the TA18 titanium alloy is enhanced, but the plasticity is reduced. Furthermore, in order to solve the plastic defects of the TA18 titanium alloy after rolling, the present invention treats the TA18 titanium alloy at its β phase transition point (T β ) After heat treatment at 25~30℃ below, quenching is performed; during the heat treatment, the α phase of the TA18 titanium alloy is recrystallized and an equiaxed α phase is formed by controlling the temperature and time of the heat treatment within the above reasonable range; during the quenching process, the β phase of the TA18 titanium alloy is transformed into a needle-shaped α′ martensite phase, that is, the microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase. The performance test of the TA18 titanium alloy after the above heat treatment was carried out, and its yield strength was 600~700MPa, the tensile strength was 700~800MPa, and the elongation after fracture was 20~30%. It can be seen that the TA18 titanium alloy after heat treatment in the above technical scheme has the characteristics of high strength and high plasticity (or toughness), and the strength and plasticity are matched, which reduces the crack sensitivity of the titanium alloy. In summary, the above technical scheme of the present invention solves the technical problem that the plasticity or toughness of the titanium alloy decreases and the crack sensitivity of the titanium alloy increases after adjusting the annealing temperature of the existing TA18 titanium alloy.
[0007] Furthermore, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, after quenching to room temperature, it also includes: The TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours, and then cooled to room temperature; The microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s Mutually.
[0008] Furthermore, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the composition of the TA18 titanium alloy is Ti-3Al-2.5V, and the content of each component is 2.5~3.5wt% aluminum, 2~3wt% vanadium, and the balance is titanium.
[0009] Furthermore, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the β phase transition point of the TA18 titanium alloy is 925~935℃.
[0010] Furthermore, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the starting recrystallization temperature is 550~600℃.
[0011] Furthermore, in the heat treatment process for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the TA18 titanium alloy is subjected to a rolling process at room temperature, comprising: The TA18 titanium alloy is subjected to a rolling treatment at 15-25° C.; In the rolling process, the total deformation of the TA18 titanium alloy is 55-60%, and the pressing amount per pass is 0.5-1 mm.
[0012] Furthermore, in the heat treatment process for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the quenching to room temperature comprises: The TA18 titanium alloy after the insulation treatment is placed in a quenching medium until the temperature of the TA18 titanium alloy reaches 15-25° C.; wherein the temperature of the quenching medium is 15-25° C., and the quenching medium includes water.
[0013] Furthermore, in the heat treatment process for regulating the strength and plasticity of the TA18 titanium alloy of the present invention, the TA18 titanium alloy is subjected to heat treatment at 25-30° C. below its β phase transformation point for 2-2.5 hours, comprising: In a vacuum environment, the TA18 titanium alloy is subjected to a heat treatment at 25-30° C. below its β phase transformation point for 2-2.5 hours; wherein the vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
[0014] Furthermore, in the heat treatment process for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours, comprising: In a vacuum environment, keeping the TA18 titanium alloy at its recrystallization start temperature for 2 to 2.5 hours; The vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
[0015] In a second aspect, the present invention provides a TA18 titanium alloy, which is obtained by heat treatment using the above-mentioned heat treatment process method for regulating the strength and plasticity of the TA18 titanium alloy, wherein the microstructure of the TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase, or the microstructure of the TA18 titanium alloy includes an equiaxed α phase, a lamellar α′ martensite phase and / or an α s Phase; the yield strength of the TA18 titanium alloy is 600~700MPa, the tensile strength is 700~800MPa, and the elongation after fracture is 20~30%.
[0016] Compared with the prior art, the beneficial effects of the TA18 titanium alloy of the present invention are the same as the beneficial effects of the heat treatment process method for regulating the strength and plasticity of the TA18 titanium alloy described in the above technical scheme, and will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a scanning electron microscope image of the TA18 titanium alloy obtained after heat treatment in Example 1 of the present invention; Figure 2 is a scanning electron microscope image of the TA18 titanium alloy obtained after heat treatment in Example 2 of the present invention; Figure 3 This is a scanning electron microscope image of the forged TA18 titanium alloy raw material of Comparative Example 1 of the present invention; Figure 4 This is a scanning electron microscope image of the TA18 titanium alloy obtained after heat treatment in Comparative Example 2 of the present invention; Figure 5 Schematic diagram of the engineering stress-engineering strain curve of the TA18 titanium alloy obtained in Examples 1 and 2 of the present invention and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0019] It should be noted that when an element is referred to as being "fixed to" or "disposed on" another element, it can be directly on the other element or indirectly on the other element. When an element is referred to as being "connected to" another element, it can be directly connected to the other element or indirectly connected to the other element.
[0020] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.
[0021] The mechanical properties of titanium alloys are extremely sensitive to their microstructures, so regulating the microstructure is an effective way to optimize the room temperature strength and plasticity of near-α titanium alloys and improve the comprehensive mechanical properties of the material. In terms of regulating the mechanical properties of TA18 titanium alloys, the existing technology mainly uses annealing treatment after cold deformation to adjust the annealing temperature of TA18 titanium alloys to obtain the best strength-plasticity match. However, while this regulation method improves the strength of the alloy, it is usually accompanied by a decrease in plasticity or toughness, increases the crack sensitivity of the titanium alloy, is not conducive to the subsequent cold forming of the TA18 titanium alloy, and limits the production and application of TA18 titanium alloys.
[0022] In order to solve the above technical problems, in a first aspect, the present invention provides a heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy, comprising: Obtaining a forged TA18 titanium alloy, wherein the microstructure of the TA18 titanium alloy includes an α phase and a β phase, with the α phase as a matrix; The TA18 titanium alloy is subjected to a rolling process at room temperature; The TA18 titanium alloy is heat treated at 25-30° C. below its β transformation point for 2-2.5 hours and then quenched to room temperature. The microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase.
[0023] In the case of adopting the above technical scheme, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, a plate-shaped titanium alloy with high strength characteristics can be obtained by rolling the forged TA18 titanium alloy. During the rolling process, the strength of the TA18 titanium alloy is enhanced, but the plasticity is reduced. Furthermore, in order to solve the plastic defects of the TA18 titanium alloy after rolling, the present invention treats the TA18 titanium alloy at its β phase transition point (T β) After heat treatment at 25~30℃ below, quenching is performed; during the heat treatment, the α phase of the TA18 titanium alloy is recrystallized and an equiaxed α phase is formed by controlling the temperature and time of the heat treatment within the above reasonable range; during the quenching process, the β phase of the TA18 titanium alloy is transformed into a needle-shaped α′ martensite phase, that is, the microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase. The performance test of the TA18 titanium alloy after the above heat treatment was carried out, and its yield strength was 600~700MPa, the tensile strength was 700~800MPa, and the elongation after fracture was 20~30%. It can be seen that the TA18 titanium alloy after heat treatment of the above technical solution has the characteristics of high strength and high plasticity (or toughness), and the strength and plasticity are matched, which reduces the crack sensitivity of the titanium alloy. For example, the temperature of the heat preservation treatment can be 25°C below the β transformation point, 27°C below the β transformation point, or 30°C below the β transformation point, and the heat preservation treatment time can be 2 hours, 2.2 hours, or 2.5 hours. In summary, the above technical solution solves the technical problem that after adjusting the annealing temperature of the TA18 titanium alloy, the plasticity or toughness of the titanium alloy decreases, and the crack sensitivity of the titanium alloy increases.
[0024] As a possible implementation mode, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, after quenching to room temperature, the method further comprises: The TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours, and then cooled to room temperature; The microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s Mutually.
[0025] In the case of adopting the above technical scheme, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, after quenching, the TA18 titanium alloy is subjected to a heat preservation treatment at its recrystallization start temperature, and the heat preservation time is controlled within the above reasonable range, so that the needle-shaped α′ martensite phase of the TA18 titanium alloy can be decomposed to form a lamellar α′ martensite phase and / or α s The original equiaxed α phase of TA18 titanium alloy remains unchanged, that is, the microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s Phase. Performance testing of the TA18 titanium alloy after heat treatment of the technical solution found that the plasticity of the TA18 titanium alloy remained almost unchanged, but the strength was further improved, which can further meet the high-strength application requirements. For example, the insulation time can be 2 hours, 2.2 hours or 2.5 hours.
[0026] It should be understood that TA18 titanium alloys with different compositions or TA18 titanium alloys with different contents of each component may have different β phase transition points (Tβ ) and the starting recrystallization temperature. For example, the β phase transformation point of the TA18 titanium alloy may be 925~935°C, and the starting recrystallization temperature may be 550~600°C; for another example, the β phase transformation point of the TA18 titanium alloy may be 925°C, 930°C or 935°C, and the starting recrystallization temperature may be 550°C, 580°C or 600°C. For example, the composition of the TA18 titanium alloy may be Ti-3Al-2.5V, and the content of each component may be 2.5~3.5wt% aluminum, 2~3wt% vanadium, and the balance is titanium. For another example, the content of each component may be 3.5wt% aluminum, 3wt% vanadium, and the balance is titanium and trace unavoidable impurities.
[0027] As a possible implementation mode, in the heat treatment process for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the TA18 titanium alloy is subjected to a rolling process at room temperature, comprising: The TA18 titanium alloy is subjected to a rolling treatment at 15-25° C.; In the rolling process, the total deformation of the TA18 titanium alloy is 55-60%, and the pressing amount per pass is 0.5-1 mm.
[0028] Under the condition of adopting the above technical scheme, the present invention can obtain the plate-shaped titanium alloy required by the composite heat treatment by cold deformation treatment (rolling treatment at room temperature) of the forged TA18 titanium alloy, and control the total deformation amount and the pressing amount of each pass of the forged TA18 titanium alloy within the above reasonable range, and effectively enhance the strength of the TA18 titanium alloy. For example, the above rolling treatment can be carried out in a double-roll plate and strip mill, the rolling treatment temperature can be 15°C, 20°C or 25°C, the total deformation amount of the TA18 titanium alloy can be 55%, 58% or 60%, and the pressing amount of the TA18 titanium alloy in each pass of the double-roll plate and strip mill can be 0.5mm, 0.8mm or 1mm.
[0029] As a possible implementation mode, in the heat treatment process for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the quenching to room temperature comprises: The TA18 titanium alloy after the insulation treatment is placed in a quenching medium until the temperature of the TA18 titanium alloy reaches 15-25° C.; wherein the temperature of the quenching medium is 15-25° C., and the quenching medium includes water.
[0030] As a possible implementation mode, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the TA18 titanium alloy is subjected to heat treatment at 25-30° C. below its β phase transformation point for 2-2.5 hours, comprising: In a vacuum environment, the TA18 titanium alloy is subjected to a heat treatment at 25-30° C. below its β phase transformation point for 2-2.5 hours; wherein the vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
[0031] In the case of adopting the above technical solution, the present invention can prevent the TA18 titanium alloy from reducing its plasticity after absorbing oxygen during the heat treatment process by performing heat preservation treatment in a vacuum environment; for example, the vacuum degree of the vacuum environment can be 1×10 -3 Pa, 1×10 -4 Pa or 1×10 -5 Pa.
[0032] As a possible implementation mode, in the heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy of the present invention, the TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours, comprising: In a vacuum environment, the TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours; The vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
[0033] In the case of adopting the above technical solution, the present invention can prevent the TA18 titanium alloy from reducing its plasticity after absorbing oxygen during the heat treatment process by performing heat preservation treatment in a vacuum environment; for example, the vacuum degree of the vacuum environment can be 1×10 -3 Pa, 1×10 -4 Pa or 1×10 -5 Pa.
[0034] In a second aspect, the present invention provides a TA18 titanium alloy, which is obtained by heat treatment using the above-mentioned heat treatment process method for regulating the strength and plasticity of the TA18 titanium alloy, wherein the microstructure of the TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase, or the microstructure of the TA18 titanium alloy includes an equiaxed α phase, a lamellar α′ martensite phase and / or an α s Phase; the yield strength of the TA18 titanium alloy is 600~700MPa, the tensile strength is 700~800MPa, and the elongation after fracture is 20~30%.
[0035] In the case of adopting the above technical scheme, the TA18 titanium alloy of the present invention is obtained by heat treatment through the above heat treatment process method for regulating the strength and plasticity of the TA18 titanium alloy. In the heat treatment process method for regulating the strength and plasticity of the TA18 titanium alloy, a plate-shaped titanium alloy with high strength characteristics can be obtained by rolling the forged TA18 titanium alloy. During the rolling process, the strength of the TA18 titanium alloy is enhanced, but the plasticity is reduced. Furthermore, in order to solve the plastic defects of the TA18 titanium alloy after the rolling process, the present invention treats the TA18 titanium alloy at its β phase transition point (T β ) After heat treatment at 25-30℃ below, quenching is performed; during the heat treatment, the α phase of the TA18 titanium alloy is recrystallized and an equiaxed α phase is formed by controlling the temperature and time of the heat treatment within the above reasonable range; during the quenching process, the β phase of the TA18 titanium alloy is transformed into a needle-shaped α′ martensite phase, that is, the microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase. Further, after quenching is completed, the needle-shaped α′ martensite phase of the TA18 titanium alloy can be decomposed to form a lamellar α' martensite phase or and / or α by heat treatment of the TA18 titanium alloy at its recrystallization start temperature and controlling the heat treatment time within the above reasonable range. s The original equiaxed α phase of TA18 titanium alloy remains unchanged, that is, the microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s The TA18 titanium alloy (after heat treatment) of the present invention is tested for performance, and it has the characteristics of high strength and high plasticity (or toughness), and the strength and plasticity are matched, which reduces the crack sensitivity of the titanium alloy.
[0036] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0037] Unless otherwise specified, the raw materials used in the following examples are commercially available. Example 1
[0038] This embodiment provides a heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy, comprising: S100, obtaining a TA18 titanium alloy forging rod, the composition of the titanium alloy is Ti-3Al-2.5V, the content of each component is 3.15wt% aluminum and 2.51wt% vanadium, and the balance is titanium and trace impurity elements; The microstructure of the titanium alloy includes α phase and β phase, with α phase as the matrix; β The phase transition point is 935℃; S200, rolling the TA18 titanium alloy forged rod in a double-roll strip mill for multiple passes at a temperature of 25° C. to obtain a titanium alloy rolled plate, the titanium alloy rolled plate having a specification of 200 mm×60 mm and a thickness of 4 mm; wherein the total deformation of the TA18 titanium alloy during the rolling process is 55%, and the pressing amount of each pass is 0.5 mm; S300, at a vacuum degree of 1×10 -3 The titanium alloy rolled plate in step S200 is subjected to solution treatment in a vacuum environment of 1000 Pa: after the furnace temperature is stabilized, the sample is placed at a temperature and kept at a furnace temperature of 910° C. for 2 hours; S400, after the insulation of step S300 is completed, the titanium alloy rolled plate is quenched to room temperature; wherein the temperature of the quenching medium is 25°C, the quenching medium is water, the heat treatment of the TA18 titanium alloy is completed, and the heat-treated TA18 titanium alloy is prepared.
[0039] After the treated TA18 titanium alloy was obtained, its initial structure was characterized by scanning electron microscopy. Figure 1 It can be seen that the initial structure of the alloy is a microstructure composed of equiaxed α phase and needle-shaped α′ martensite phase, among which the content of equiaxed α phase is 26.8%, and the average grain size is 7.19±2.52μm. Figure 1 Medium α p represents the initial α phase (i.e., equiaxed α phase), and α′ represents the α′ martensite phase.
[0040] The mechanical properties of the TA18 titanium alloy prepared in this embodiment were measured according to GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 5 As shown, the results show that its yield strength is 620MPa, tensile strength is 727MPa, and elongation after fracture is 26.2%, which has the characteristics of high strength and high plasticity. Example 2
[0041] This embodiment provides a heat treatment process method for regulating the strength and plasticity of TA18 titanium alloy, comprising: S100, obtaining a TA18 titanium alloy forging rod, the composition of the titanium alloy is Ti-3Al-2.5V, the content of each component is 3.15wt% aluminum and 2.51wt% vanadium, and the balance is titanium and trace impurity elements; The microstructure of the titanium alloy includes α phase and β phase, with α phase as the matrix; β The phase transition point is 935°C and the recrystallization start temperature is 550°C; S200, rolling the TA18 titanium alloy forged rod in a double-roll strip mill for multiple passes at a temperature of 25° C. to obtain a titanium alloy rolled plate, the titanium alloy rolled plate having a specification of 200 mm×60 mm and a thickness of 4 mm; wherein the total deformation of the TA18 titanium alloy during the rolling process is 55%, and the pressing amount of each pass is 0.5 mm; S300, at a vacuum degree of 1×10 -3 The titanium alloy rolled plate in step S200 is subjected to solution treatment in a vacuum environment of 1000 Pa: after the furnace temperature is stabilized, the sample is placed at a temperature and kept at a furnace temperature of 910° C. for 2 hours; S400, after the heat preservation in step S300 is completed, the titanium alloy rolled plate is quenched to room temperature; wherein the temperature of the quenching medium is 25° C., and the quenching medium is water; S500, after the quenched titanium alloy rolled plate is kept at a temperature of 550° C. for 2 hours, it is air-cooled to room temperature to complete the heat treatment of the TA18 titanium alloy, and the heat-treated TA18 titanium alloy is prepared.
[0042] After the treated TA18 titanium alloy was obtained, its initial structure was characterized by scanning electron microscopy. Figure 2 It can be seen that the initial structure of the alloy is equiaxed α phase, lamellar α' martensite phase and α s The microstructure of the phase composition is shown in Figure 2, among which the content of equiaxed α phase is 29.5% and the average grain size is 6.94±2.31μm. Figure 2 Medium α p represents the initial α phase (i.e., equiaxed α phase), α′ represents the α′ martensite phase, and α s Represents α s Mutually.
[0043] The mechanical properties of the TA18 titanium alloy prepared in this embodiment were measured according to GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 5 As shown, the results show that the yield strength is 686MPa, the tensile strength is 756MPa, and the elongation after fracture is 28.0%. Compared with Example 1, the plasticity of the titanium alloy after heat treatment in this example does not change much, but the strength is significantly improved.
[0044] Comparative Example 1 In this comparative example, the TA18 titanium alloy forged rod in step S100 of Example 1 is not subjected to heat treatment, and the performance test is directly performed.
[0045] The initial microstructure of the TA18 titanium alloy forging rod of this comparative example was characterized by scanning electron microscopy. Figure 3 As shown, from Figure 3It can be seen that the microstructure of the titanium alloy forged rod consists of a matrix α phase and a uniformly distributed β phase, and there is no α′ martensite phase in the above embodiment. Figure 3 Medium α p represents the initial α phase, α′ represents the α′ martensite phase, and β represents the β phase.
[0046] The mechanical properties of the titanium alloy forging bar of this comparative example were measured according to GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method". The engineering stress-engineering strain curve is shown in the attached figure. Figure 5 As shown, the results show that its yield strength is 530MPa, the tensile strength is 632MPa, and the elongation after fracture is 33.3%. It can be seen that compared with Example 1, the strength of the titanium alloy that has not been subjected to water quenching heat treatment is lower.
[0047] Comparative Example 2 The heat treatment process for regulating the strength and plasticity of TA18 titanium alloy in this comparative example is basically the same as that in Example 2, except that, in step S300, the titanium alloy rolled plate is kept at a furnace temperature of 920°C (15°C below the β phase transformation point) for 2 hours.
[0048] The TA18 titanium alloy after heat treatment in this comparative example was characterized by scanning electron microscopy. Figure 4 As shown, from Figure 4 It can be seen that the initial structure of the titanium alloy is a microstructure of needle-shaped α' martensite, with almost no equiaxed α phase. Figure 4 Here, α′ represents α′ martensite phase.
[0049] According to GB / T228.1-2010 "Tensile test of metallic materials Part 1: Room temperature test method", the engineering stress-engineering strain curve of the TA18 titanium alloy after heat treatment in this comparative example is shown in the attached figure. Figure 5 As shown, the results show that its yield strength is 760MPa, tensile strength is 830MPa, and elongation after fracture is 16.8%. Compared with the above-mentioned Example 1 and Example 2, the TA18 titanium alloy after heat treatment in this comparative example lacks the equiaxed α phase to provide plasticity for its interface, resulting in a sharp decrease in plasticity while increasing strength.
[0050] It can be concluded from the above embodiments and comparative examples that the TA18 titanium alloy is β) and then quenched. The microstructure of the TA18 titanium alloy includes equiaxed α phase and needle-shaped α′ martensite phase, which can simultaneously improve the strength and plasticity of the titanium alloy, and the strength and plasticity are matched, reducing the crack sensitivity of the titanium alloy; specifically, its yield strength reaches 600~700MPa, the tensile strength reaches 700~800MPa, and the elongation after fracture reaches 20~30%. Further, after the quenching is completed, the titanium alloy is kept at its recrystallization start temperature for 2~2.5 hours and then cooled to room temperature. In this process, the needle-shaped α′ martensite phase of the TA18 titanium alloy can be decomposed to form a lamellar α' martensite phase or and / or α s The original equiaxed α phase of TA18 titanium alloy remains unchanged, and the microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s Phase, while the plasticity of the titanium alloy containing equiaxed α phase and acicular α′ martensite phase remains almost unchanged, its strength is further improved, and under the condition that its plasticity reaches the requirement, it can further meet the application needs of high strength.
[0051] In the description of the above embodiments, specific features, structures, materials or characteristics may be combined in a suitable manner in any one or more embodiments or examples.
[0052] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A heat treatment process for regulating the strength and plasticity of TA18 titanium alloy, characterized in that: include: Obtaining a forged TA18 titanium alloy, wherein the microstructure of the TA18 titanium alloy includes an α phase and a β phase, with the α phase as a matrix; The TA18 titanium alloy is subjected to a rolling process at room temperature; The TA18 titanium alloy is heat treated at 25-30° C. below its β transformation point for 2-2.5 hours and then quenched to room temperature. The microstructure of the obtained TA18 titanium alloy includes an equiaxed α phase and a needle-shaped α′ martensite phase.
2. The heat treatment process for regulating the strength and plasticity of TA18 titanium alloy according to claim 1, characterized in that: After the quenching to room temperature, the process further comprises: The TA18 titanium alloy is kept at its recrystallization start temperature for 2 to 2.5 hours, and then cooled to room temperature; The microstructure of the obtained TA18 titanium alloy includes equiaxed α phase, lamellar α' martensite phase and / or α s Mutually.
3. The heat treatment process for regulating the strength and plasticity of TA18 titanium alloy according to claim 2, characterized in that: The composition of the TA18 titanium alloy is Ti-3Al-2.5V, and the content of each component is 2.5-3.5wt% aluminum, 2-3wt% vanadium, and the balance is titanium.
4. The heat treatment process for adjusting the strength and plasticity of TA18 titanium alloy according to claim 3 is characterized in that: The β phase transition point of the TA18 titanium alloy is 925~935°C.
5. The heat treatment process for regulating the strength and plasticity of TA18 titanium alloy according to claim 4, characterized in that: The recrystallization start temperature is 550-600°C.
6. The heat treatment process for adjusting the strength and plasticity of TA18 titanium alloy according to claim 5, characterized in that: The step of rolling the TA18 titanium alloy at room temperature comprises: The TA18 titanium alloy is subjected to a rolling treatment at 15-25° C.; In the rolling process, the total deformation of the TA18 titanium alloy is 55-60%, and the pressing amount per pass is 0.5-1 mm.
7. The heat treatment process for adjusting the strength and plasticity of TA18 titanium alloy according to claim 6, characterized in that: The quenching to room temperature comprises: The TA18 titanium alloy after the insulation treatment is placed in a quenching medium until the temperature of the TA18 titanium alloy reaches 15-25° C.; wherein the temperature of the quenching medium is 15-25° C., and the quenching medium includes water.
8. The heat treatment process for regulating the strength and plasticity of TA18 titanium alloy according to claim 1, characterized in that: The step of heat-treating the TA18 titanium alloy at 25-30° C. below its β phase transformation point for 2-2.5 hours comprises: In a vacuum environment, the TA18 titanium alloy is subjected to a heat treatment at 25-30° C. below its β phase transformation point for 2-2.5 hours; wherein the vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
9. The heat treatment process for adjusting the strength and plasticity of TA18 titanium alloy according to claim 2, characterized in that: The step of keeping the TA18 titanium alloy at its recrystallization start temperature for 2 to 2.5 hours comprises: In a vacuum environment, keeping the TA18 titanium alloy at its recrystallization start temperature for 2 to 2.5 hours; The vacuum degree of the vacuum environment is equal to or lower than 1×10 -3 Pa.
10. A TA18 titanium alloy, characterized in that: The TA18 titanium alloy is obtained by heat treatment using the heat treatment process for regulating the strength and plasticity of the TA18 titanium alloy according to any one of claims 1 to 9, wherein the microstructure of the TA18 titanium alloy comprises an equiaxed α phase and a needle-shaped α′ martensite phase, or the microstructure of the TA18 titanium alloy comprises an equiaxed α phase, a lamellar α′ martensite phase and / or an α′ martensite phase. s Phase; the yield strength of the TA18 titanium alloy is 600~700MPa, the tensile strength is 700~800MPa, and the elongation after fracture is 20~30%.
Citation Information
Cited By
Ti65 alloy and heat treatment method and application thereof
CN121228144A